News cartography and epistemic authority in the era of big data: Journalists as map-makers, map-users, and map-subjects. (February 2020) - Usher, Nikki
Although the destabilization of journalism's epistemic authority has been widely discussed, one critical element has been underexplored—the role of place. For journalists, claiming provenance over "where" has enabled control over a domain of knowledge, and one key means for doing so has been through news cartography, now rendered digitally. However, digital news cartography (digital news maps) exposes journalists' epistemic authority to new challenges, from reliance on big data collected by others to maps about journalism itself that show journalists' diminished authority over place. The case of digital news maps offers a chance to interrogate how journalists know what they know and how they know it and, more broadly, begs the question of how place and mapping must be considered in new media research.